2021
DOI: 10.3389/fpsyg.2021.539582
|View full text |Cite
|
Sign up to set email alerts
|

When Work Conflicts With Personal Projects: The Association of Work-Life Conflict With Worker Wellbeing and the Mediating Role of Mindfulness

Abstract: The negative emotional and health effects of work-life conflict (WLC) have been demonstrated in numerous studies regarding organizational psychology and occupational health. However, little is known about WLC’s relationship with positive wellbeing outcomes, including emotional, psychological, and social aspects of workers’ thriving. Furthermore, the mediating processes underlying the effects of WLC remain mostly unknown. The current study investigated the associations of perceived time- and strain-based WLC wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Prior research has provided empirical evidence supporting the role of mindfulness in promoting work-life balance. For instance, Pacheco et al (2021) found that individuals practicing mindfulness reported lower work-life conflict and greater satisfaction in both work and personal life domains. Similarly, Daniel et al (2022) demonstrated that mindfulness practices can reduce the negative spillover effects of work stress into personal life, thereby fostering a more harmonious work-life integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has provided empirical evidence supporting the role of mindfulness in promoting work-life balance. For instance, Pacheco et al (2021) found that individuals practicing mindfulness reported lower work-life conflict and greater satisfaction in both work and personal life domains. Similarly, Daniel et al (2022) demonstrated that mindfulness practices can reduce the negative spillover effects of work stress into personal life, thereby fostering a more harmonious work-life integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DWCs' activities are characterized by work overload, low worker involvement in decision-making, and low levels of social support, all of which can have an impact on their psychological health and well-being (ILO, 2019b;Pacheco, Coulombe, & Meunier, 2021;Takala et al, 2012). In Ghana for instance, in Ho municipality, DWCs who work for waste companies are perceived by the public as a job for people of low socioeconomic status, have inadequate legal protection, and are disrespected.…”
Section: Health and Safety In The Waste Environmentmentioning
confidence: 99%
“…Several of the case examples found reports of DWCs keeping a low profile and hiding their occupation from their communities to protect the safety and well-being of their families (Marello & Helwege, 2018;Mensah-Akoto & Matsui, 2022;Vidanaarachchi et al, 2006). In addition, decreased well-being and reduced job satisfaction of employees negatively affect the effectiveness of waste management companies (Gyekye, 2006;Pacheco et al, 2021;Ramos, McGinley, & Carlo, 2021;Shan, Liu, Gu, & Zhao, 2022). Furthermore, some DWCs are prone to social vices such as alcoholism and drug addiction to cope with negative working conditions.…”
Section: Health and Safety In The Waste Environmentmentioning
confidence: 99%